(±)-(rel-3R,3′R)-1,1′-Dimethyl-3,3′-bipyrrolidine-2,2′-dithione - Madeley, Lee G. (International Union of Crystallography, 2012)
The asymmetric unit of the racemic title compound, C(10)H(16)N(2)S(2), a C (2)-symmetric bis(thiolactam), contains one half-molecule, the complete molecule being generated by a twofold axis symmetry operation. The five-membered ring is nearly planar, with a maximum deviation of 0.025 (1) Å. In the crystal, the molecules are linked via weak C—H⋯S interactions, forming infinite chains along the b-axis direction.